Dynamic changes of inflammatory markers and their effects on the prognosis of patients with laryngeal and hypopharyngeal cancer submitted to total pharyngolaryngectomy - Azevedo, Cátia (2022)
Introduction: The use of prognostic markers to decide the most appropriate therapies to perform in each case is assumed as one of the pillars of the approach to the patient with squamous cell carcinoma (SCC) of the hypopharynx and larynx. In addition to the clinical and pathological stage determined by the classification system TNM, there is evidence that the tumor-related systemic inflammatory response (SIR) has implications for tumor aggressiveness and progression. However, its value as an independent prognostic factor remains ambiguous. Aims: To analyze the tumor SIR, its perioperative dynamic changes and after adjuvant treatment and its prognostic value in patients with SCC of the larynx and hypopharynx undergoing total pharyngolaryngectomy. Methods: Retrospective analysis of clinico- pathological data of patients undergoing total pharyngolaryngectomy between January 2013 and December 2018 in a tertiary-level hospital. SIR was assessed using the following parameters: lymphocyte-monocyte ratio (LMR), platelets-lymphocyte ratio (PLR), neutrophil-lymphocyte ratio (NLR) and systemic immuno-inflammatory index (SII). Kaplan-Meier analysis and Cox regression were used to analyze survival outcomes and associated risks. Results: 59 patients were included in the study, with a mean age of 59.2 years. The mean follow- up time was 49.2 months. Preoperative PLR was the best predictor of overall survival (OS) at 5 years (area under the curve (AUC) 0.796, p<0.005). The optimal cutoff value was determined for each inflammatory parameter analyzed preoperatively, postoperatively and after adjuvant treatment (LMR: 2.6, 2.8 and 2.2, respectively; PLR: 125.0, 162.6 and 57.2, respectively; NLR: 2.3, respectively; 2.3, 2.8 and 3.9, respectively; SSI: 931.4, 732.8 and 931.43, respectively). Multivariate survival analysis showed that OS and distant metastasis-f ree survival (MFS) were statistically lower in patients with preoperative PLR >125.0 (HR 4.39, p<0.005 and HR 17.65, p <0.005, respectively). There was a significantdecrease in SIR after complete treatment with surgery with or without adjuvant chemoradiation. However, the pattern of parameters variation with treatments had no influence on OS or MFS. Patients with preoperative LPR >125.0 tend to have higher NLR and SII (p<0.005), although these did not prove to be independent predictors of survival. Conclusions: A high preoperative PLR was significantly associated with worse OS and MFS in patients undergoing total pharyngolaryngectomy. Still, the use of this marker in our current clinical practice to predict postoperative outcomes must be performed in a critical way.